Why study the cytochrome P4503A (CYP3A) family? - Schuetz, Erin (Henry Stewart Talks, 2007)
Role of CYP3A4, CYP3A5 and CYP3A7 in drug metabolism, Gene expression, Molecular mechanisms of regulation, Enzyme induction and inhibition, Polymorphic variation, Inter-individual variation, Drug-drug interactions
Reviewed at 2015/08/11